Pembinaan Ibu Balita dalam Pencegahan Stunting di Desa Kelusa, Payangan, Gianyar - Komang Triyani Kartinawati; Luh Gede Pradnyawati; Ni Putu Diah Witari (Warmadewa University Press, 2023)
Village of Kelusa is located in the district of Payangan, region of Gianyar, province of Bali. Geographically, the majority of Kelusa’s area is utilized for agriculture with irrigation as the water system. This agriculture is the source of local-based products for daily consumption of Kelusa’s population. Food security is one essential factor to prevent the nutritional disorder, such as in stunting. However, regarding the report from Public Health Office of Gianyar in the 2022, there was still 278 stunted toddlers (13,7%) and 173 stunted in below two years of age children (21,5%) in the area of Payangan. Through analysis and observation, there were some problems found in the village of Kelusa, including the lack of mother’s knowledge on stunting and its prevention, processing healthy weaning food, also preparing and serving weaning food to increase appetite when the child is sick. Regarding these problems, an empowerment was conducted to the community partners, which were the toddlers’ mothers, about stunting and its prevention, also the management of weaning food which is suited to the child’s age. The empowerment was integrated with the faculty students’ learning activites called Community Oriented Medical Education, in which every toddler’s family was accompanied by one faculty student continuously during the first 1000 days of life. After the health education was given, there was a 44% increase in post-test score compared to the pretest. Regarding this result, there was a significant rise of knowledge in toddlers’ mothers after the implementation of health education. Health promotion can give an impact in the mother’s knowledge about stunting, preventing stunting, and managing weaning food. These increase of knowledge and perspective would construct positive attitude and behavior in preventing stunting and managing healthy weaning food. The continuity of health education and workshop on the management of healthy weaning food to optimize the first 1000 days of life should be integrated to the community-based health effort (UKBM), such as in Posyandu and Poskesdes. Moreover, these programs can be implemented to the targeted population, such as pregnant mother and toddler’s mother, as well as the posyandu and village cadres to increase their competencies in preventing stunting on toddlers.